Pengaruh Media Dakota terhadap Hasil Belajar FPB dan KPK Pada Siswa Kelas IV SDN Dukuh Menanggal I/424 Surabaya - Lailattul Febriyanti; Dian Kusmaharti; Via Yustitia (LP. Ma'arif Janggan Magetan, 2023)
The written research was motivated by low student learning outcomes in FPB and KPK material. The purpose of this written research is to determine the effect of using Dakota media in improving FPB and KPK learning outcomes for class IV students at SDN Dukuh Menangal I/24 Surabaya. This type of written research uses experimental procedures and quantitative research strategies. The design of this research is a posttest-only control design. The population in this study was all fourth grade students at SDN Dukuh Menanggal 1/424 Surabaya. The samples used were class IV B students as the control class, totaling 25 students and class IV C students as the experimental class, totaling 24 students. Utilizing tests is a method of collecting data for written learning. Statistical tests include homogeneity, normality, and t test in testing hypotheses as a data analysis method. Based on the research results and discussion, the conclusion is that there is an influence of Dakota media on FPB and KPK learning outcomes for class IV students at SDN Dukuh Menanggal 1/424 Surabaya. The results of this research can be used as a consideration for implementing Dakota media in elementary schools.